Incidence Rates of Cervical Carcinoma Among First- and Second-Generation Women of North African Origin in Israel. Issue 9 (1st November 2009) - Menczer, Joseph; Barchana, Micha; Chetrit, Angela; Liphshitz, Irena; Sadetzki, Siegal
Abstract : Objectives: To evaluate the incidence rates of cervical cancer by ethnic origins and compare these rates between first- and second-generation women of North African origin. Methods: Data of all cervical carcinoma of Jewish women during 2000 to 2005 were obtained from the National Cancer Registry. Standardized incidence ratios for each ethnic origin category were calculated and compared using Poisson regression. Results: During the study period, 938 patients were examined. The standardized incidence ratios of North African-born women and of Israeli-born women of North African descent were significantly higher compared with those of women of other origins. Conclusions: The persistence of a higher risk of cervical cancer in Israeli Jewish women of North African descent compared with those of other origins may suggest that genetic factors are involved in the etiology of this neoplasm.